The Beatryce prophecy - DiCamillo, Kate (Candlewick Press, 2021)
After nursing an abandoned child back to health in the monastery where he lives, Brother Edik realizes she is Beatryce, a girl who holds the keys to a prophecy he wrote long ago, which compels Beatryce to embark on a quest to find out who she is.